Notes on powdery mildew of evergreen spindle Euonymus japonicus in Iran - Mehrdad Abbasi; Uwe Braun (Journal of Crop Protection, 2020)
Since the beginning of the 20th century, several scientific names have been used for the causal agent of powdery mildew on evergreen spindle Euonymus japonicus. The nomenclature of this powdery mildew is reviewed and using Erysiphe euonymicola as current name for the species is suggested. Information on the history of occurrence, natural host range and distribution of E. japonicus powdery mildew in Iran is provided. Morphological differences between E. euonymicola and E. euonymi, a powdery mildew on other species of Euonymus in Europe is discussed.